2008
DOI: 10.1021/ef700711q
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pt/WOx−ZrO2Catalysts for the Production of Reformulated Fuels by Isomerization−Cracking of Medium Length C8−C12Paraffins

Abstract: The effect of the temperature of calcination of the support on the structural properties of ZrO2 and on the activity of the acid and metal functions of a Pt/WO x −ZrO2 catalyst used in the isomerization−cracking of medium length paraffinic C8−C12 cuts was studied. n-Octane was used as model molecule. The calcination temperature was varied in order to change the metal/acid balance and to increase the yield of the reaction to isoparaffins of high octane number. Four supports were prepared by impregnating Zr(OH)4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It has been reported elsewhere [20,23] that the highest activity of Pt/WO 4 2-/ ZrO 2 catalysts is reached when tungstated zirconia is calcined at 700°C prior to Pt deposition. However, according to Hino and Arata [21], the most active bifunctional catalysts are obtained after the calcination of tungstated zirconia at 800 and 850°C.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported elsewhere [20,23] that the highest activity of Pt/WO 4 2-/ ZrO 2 catalysts is reached when tungstated zirconia is calcined at 700°C prior to Pt deposition. However, according to Hino and Arata [21], the most active bifunctional catalysts are obtained after the calcination of tungstated zirconia at 800 and 850°C.…”
Section: Introductionmentioning
confidence: 95%
“…Tungstated zirconia based catalysts for the isomerization of heavier paraffins are of particular interest [6,[14][15][16][17][18][19][20]. They exhibit catalytic activity slightly lower than that of sulfated zirconia based catalysts, but have greater isomerization selectivity [2,3,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This test confirmed the high activity and stability of the bi-promoted (WO 3 and SO 2 À 4 ) Pt on zirconia catalyst, producing an isomerate with the highest molar ratio of branched C 4 -C 7 to total branched products. 509 The acidity of the bi-promoted catalyst could be regulated by the amount of WO 3 in the catalyst. In addition to the Brønsted-toLewis acid ratio, the calcination temperature also had a pronounced effect on the final metal-to-acid site balance of the catalysts.…”
Section: Bifunctional Zirconia-based Hcr Catalystsmentioning
confidence: 99%
“…The problem of designing catalysts for the low temperature isomerization of hydrocarbon fractions including long chain alkanes has stirred considerable attention to acid catalyst systems based on zirconia modified with tungstate anions [2,5,[8][9][10][11][12]. It has been shown that their catalytic properties depend on the method of preparation of the hydroxide precursor, the amount of anions, the method of their introduc tion into the catalyst, calcination temperature, and other preparation conditions [2,8,9,12,13].…”
mentioning
confidence: 99%